Online Consumer Review, Time Pressure, and Positive Emotions on Purchase Decisions for Online Shopping - Rahyuniati Setiawan; Fitrin Rawati Suganda; Rini Apridaningsih (Entrepreneurship Faculty, Universitas Garut, 2023)
This study aimed to determine the effect of online consumer reviews, time pressure, and positive emotions on purchase decisions to shop online at Lazada among millennials in the Garut Regency. The analysis method in this study used Structural Equation Modeling and the SmartPLS 3.0 software program. The population in this study are millennials in Indonesia who have shopped online at Lazada aged 24-35 years. This study used a sampling technique involving 100 respondents. The research shows that online consumer reviews and time pressures influence purchase decisions.